Association between ATP binding cassette gene member 1 polymorphism and glucocorticoid response in children with immune thrombocytopenia. Issue 28 (15th July 2022) - Zakaria, Marwa; Hassan, Tamer; Fawzy, Amal; Fathy, Manar; Abdelazeem, Mahmoud; Magdy Abdelnour, Hanim; Abdelstar, Eman; Nafea, Alaa; Ali, Ahmed A.
Abstract : ATP binding Cassette gene member 1 (ABCB1) polymorphism has been incriminated in susceptibility to many malignant, infectious and autoimmune diseases. Recently, it was reported that ABCB1 polymorphisms might have a link to disease progression as well as response to therapy. We aimed to study the association between ABCB1 gene polymorphism and glucocorticoid response in children with newly diagnosed immune thrombocytopenia (ITP). A case control study was conducted on 90 newly diagnosed children with ITP and 90 healthy controls over a period of 1 year. ABCB1 (C3435T) polymorphism was determined by restriction fragment length polymorphism-polymerase chain reaction (RFLP-PCR) in patients and controls. There was no significant difference between patients and controls as regards to frequency of different ABCB1 genotypes (CC, CT, and TT genotypes were 44.4%, 36.7%, and 18.9% respectively in patients and 48.9%, 38.9%, and 12.2% respectively in controls, P value = 0.18). 80% of patients who received steroids alone or steroids in combination with intravenous immunoglobulin showed complete recovery. There was highly significant relationship between ABCB1 genotypes and response to steroids where 55 % of responders had CC (wild) genotype while 40 % of nonresponders had TT (mutant) genotype. We concluded that ABCB1 gene polymorphism may contribute to the response to steroids in Egyptian children with ITP where patients with homozygous CC genotype responded better to steroids than patients with homozygous TT genotype. These results may help us choose the appropriate initial treatment in these children.